Soldagem de tubos centrifugados brutos de fundição e carburizados da liga 35Cr45NiNb: microestrutura e propriedades mecânica em tração e fluência - Corsi, Waleska Laisa (Universidade Federal de São Carlos, 2024)
The 35Cr45NiNb alloy is widely used in hydrocarbon cracking furnaces due to its excellent resistance to oxidation and creep. However, this material is susceptible to carburization, which causes deterioration of mechanical properties and makes it necessary to replace the carburized sections. The remaining tubes in the equipment are eventually in an aged and/or carburized condition, therefore, they have low weldability, making it difficult to join new tubes, and compromising the mechanical performance of the weld. The objective of this work was to evaluate the effects of the welding process on the mechanical properties in tensile and creep of as cast and carburized 35Cr45NiNb tubes. The joining of the as cast segments (B) and tubes with approximately six years of use (C) was carried out using the Gas Tungsten Arc Welding (GTAW) technique, resulting in the joints B-B, B-C and C-C. The micrographs of the weld joint obtained by scanning electron microscopy (SEM) showed the growth of precipitates in the heat affected zones (HAZs), mainly in those located between segments C and the weld metal (WM), which acquired sizes relatively larger than those of the base metal (BM). These microstructural heterogeneities, combined with those pre-existing in the BM due to aging and carburization, caused a gradual reduction in the tensile strength and elongation at room temperature, as well as a decrease in the creep failure time (CFT) at 1100 ºC and 16 MPa.
Weld of as cast and carburized centricast tubes of 35Cr45NiNb alloy: microstructure and mechanical properties in tensile and creep
Keywords: Ligas resistentes ao calor; Soldagem; Fluência; Carburização; Microestrutura; Heat resistant alloys; Welding; Creep; Carburization; Microstructure; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::INSTALACOES E EQUIPAMENTOS METALURGICOS; 9. Indústria, Inovação e Infraestrutura